Hyperglycemia in Streptozotocin-Induced Diabetes Leads to Persistent Inflammation and Tissue Damage Following Uveitis Due to Reduced Levels of Ciliary Body Heme Oxygenase-1 - Settimio Rossi; Michele D'Amico; Annalisa Capuano; Mary Romano; Pasquale Petronella; Clara Di Filippo (Mediators of Inflammation)
This study investigated the heme oxygenase-1 (HO-1) and the endotoxin-induced uveitis (EIU) in diabetic streptozotocin (STZ)-hyperglycemic rats. STZ-hyperglycemic rats had impaired levels of the enzyme HO-1 within the ciliary bodies if compared with the nondiabetic rats. STZ-hyperglycemic rats also predisposed the eye to produce high levels of both the cytokines IL-1β and CXCL8. Subsequent EIU further and significantly (P<.01) increased the cytokines production, an effect partly prevented by hemin treatment. Most importantly, hemin, an inducer of heme oxygenase expression and activity, recovered the huge number of infiltrated polymorphonuclear leukocytes PMN within the ciliary bodies associated with STZ-hyperglycemic state and EIU damage. Impairment of the stress-sensitive enzyme HO-1 in STZ-hyperglycemic rats increases and prolongs the inflammatory response to EIU.